2021
DOI: 10.1088/1361-6471/abeb59
|View full text |Cite
|
Sign up to set email alerts
|

Study of transverse spherocity and azimuthal anisotropy in Pb–Pb collisions at sNN=5.02 TeV using a multi-phase transport model

Abstract: Transverse spherocity is an event shape observable having a unique capability to separate the events based on their geometrical shapes. Recent results from experiments at the LHC suggest that transverse spherocity is an important event classifier in small collision systems. In this work, we use transverse spherocity for the first time in heavy-ion collisions and perform an extensive study on azimuthal anisotropy of charged particles produced in Pb–Pb collisions at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 47 publications
(78 reference statements)
4
30
0
Order By: Relevance
“…This is a first attempt to explore the sensitiveness of the global observables in heavy-ion collisions, to the event topology and hence the underlying particle production dynamics. In our recent study [1], we found that the anisotropic flow strongly depends on transverse spherocity in heavy-ion collision systems. Thus, it would be interesting to see how the global properties, often studied in heavy-ion collisions, vary as a function of transverse spherocity.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…This is a first attempt to explore the sensitiveness of the global observables in heavy-ion collisions, to the event topology and hence the underlying particle production dynamics. In our recent study [1], we found that the anisotropic flow strongly depends on transverse spherocity in heavy-ion collision systems. Thus, it would be interesting to see how the global properties, often studied in heavy-ion collisions, vary as a function of transverse spherocity.…”
Section: Introductionmentioning
confidence: 82%
“…The AMPT settings in the current work, are the same as reported in Ref. [1,12]. For the input of impact parameter values for different centralities in Pb-Pb collisions, we have used Ref.…”
Section: A a Multi-phase Transport (Ampt) Modelmentioning
confidence: 99%
“…Here, a and b denote two separate particles in a pair. In this study, we have taken charged particles in |η| < 2.5 and p T > 0.5 GeV/c to be consistent with previous studies [52,53]. The 1D correlation function is given as,…”
Section: Elliptic Flowmentioning
confidence: 99%
“…ψ n is the n th harmonic event plane angle [51]. To reduce the non-flow effects, a two-particle correlation method [52,53] can be adopted to estimate the elliptic flow. The correlation function between two particles is obtained in relative pseudorapidity (∆η = η a − η b ) and relative azimuthal angle (∆φ = φ a − φ b ).…”
Section: Elliptic Flowmentioning
confidence: 99%
“…In this work [10], we report the first implementation of transverse spherocity in heavy-ion collisions using a multi-phase transport (AMPT) model [11]. We have performed an extensive study of azimuthal anisotropy of charged particles produced in Pb-Pb collisions at √ s NN = 5.02 TeV as a function of transverse spherocity (S 0 ).…”
Section: Introductionmentioning
confidence: 99%